Vertical ground reaction force analysis during gait with unstable shoes - Giulia Pereira; Aluísio Otavio Vargas Avila; Rudnei Palhano
AbstractIntroduction Footwear is no longer just an accessory but also a protection for the musculoskeletal system, and its most important characteristic is comfort.Objectives This study aims to identify and to analyze the vertical ground reaction force in barefoot women and women with unstable shoes.Methodology Five women aged 25 ± 4 years old and mass of 50 ± 7 kg participated in this study. An AMTI force plate was used for data acquisition. The 10 trials for each situation were considered valid where the subject approached the platform with the right foot and at the speed of 4 km/h ± 5%. The instable shoe of this study is used in the practice of physical activity.Results The results showed that the first peak force was higher for the footwear situation, about 5% and significant differences between the barefoot and footwear situation. This significant difference was in the first and second peaks force and in the time of the second peak.Conclusion The values showed that the footwear absorbs approximately 45% of the impact during gait.